INOVASI PERAN PEMERINTAH DESA DALAM PROGRAM “DESA EKONOMI KREATIF” DI DESA SEJIRAM, KECAMATAN TEBAS, KABUPATEN SAMBAS - Yuniarsih, Rulida (CV. Lafadz Jaya, 2024)
This paper reviews the initiative of the government of Sejiram Village, Tebas Sub-district, Sambas Regency, in developing creative economic potential through the Creative Economy Village Program. In this program, the village government acts as a coordinator that connects village communities, government agencies, the private sector and non-government organizations to create an enabling environment for creative economic growth at the local level. This research aims to develop a sustainable model or framework for creative economy development in Sejiram Village by applying principles of sustainability and innovation that strengthen the role of the village government. The method used is field research, which allows observation and analysis of specific behaviors of subjects in their natural environment. Preliminary findings show that the Creative Economy Village Program in Sejiram Village has great potential in supporting sustainable village development through collaboration between the village government, community, and private sector. The program is expected to serve as a model for other villages in Indonesia in improving community welfare through the development of a locally-based creative economy.